Development, Innovation and Enlightenment - Khakimova Sarvinoz Sharifjan's Qizi (Genius Journals, 2023)
In this article, today's efforts to further improve the quality of life in our country, ideas about innovative ideas being created and the concepts of enlightenment, which are the key to human development, and instructions about the analysis of these ideas were given.
Keywords: society; development; innovation; spirituality